One Health approach and zoonotic diseases in Indonesia: Urgency of implementation and challenges - Adnyana, I MDM.; Utomo, Budi; Eljatin, Dwinka S.; Sudaryati, Ni LG. (Narra Sains Indonesia, 2023)
The urgency of implementing the One Health approach to overcome zoonotic diseases cannot be overstated. By recognizing the interconnectedness of human health, animal health, and the environment, we can effectively prevent and respond to emerging infectious disease threats. This correspondence provides information on the importance of generating research on zoonotic diseases, especially in Indonesia, where research is still relatively scarce. The Indonesian government has taken steps to implement the One Health by establishing the One Health Coordinating Unit and the National Zoonosis Committee; however, implementation has not been optimal. The urgency and challenges are focused on critical implementation aspects in the community. The urgency of implementing One Health includes that Indonesia has experienced several outbreaks of zoonotic diseases, high environmental degradation, and the antimicrobial resistance (AMR) issue in Indonesia has increased. The challenges faced in implementing One Health are overcoming fragmentation due to incohesive communication between important sectors, securing funding and resource investment, aligning policies to eliminate regulation barriers, capacity building to increase awareness and professionals, and addressing critical socioeconomic factors. By prioritizing implementing the One Health approach and addressing existing challenges, Indonesia can build a more resilient and integrated system to protect the well-being of all species, protect ecosystems, and prevent the devastating effects of zoonotic diseases on global health. In this review, we present the urgency of One Health implementation and its challenges comprehensively.